Measuring Learning in the Blink of an Eye: Adolescents' Neurophysiological Reactions Predict Long-Term Memory for Stories - Gotlieb, Rebecca J. M.; Yang, Xiao-Fei; Immordino-Yang, Mary Helen (Frontiers in Education, 2021)
Anticipating what adolescents will remember is a common goal in education research, but what tools allow us to predict adolescents’ memory without interrupting the learning process as it naturally occurs? To attempt to identify neurophysiological markers of deep processing that may predict long-term retention, here we conducted an exploratory study by adding a cued recall probe to the last wave of data collection in a longitudinal psychosocial and neuroimaging study of 65 urban adolescents. Five years prior, and again three years prior, participants had reacted to the same emotionally evocative true stories during a videotaped interview that allowed us to measure eye blink rate (EBR), and again during fMRI scanning. We analyzed EBR and neural data from the initial story exposure. We found that memory for a story was predicted by both EBR (a proxy for striatal dopamine) and default mode network neural activity to that story (involved in integrative memory and processing of emotional feelings). EBR and default mode network activity were uncorrelated and explained additive variance. Though more work is needed, our study contributes preliminary supportive evidence linking EBR and neural activity trial-by-trial to long-term memory in a naturalistic task. The analyses suggest that including EBR, a non-invasive, portable and inexpensive measure that can be coded from high-quality video recording, could be useful in future studies of adolescents’ learning.